From arithmetic to metaphysics a path through philosophical logic - Florio, Ciro de; Giordani, Alessandro; Galvan, Sergio, 1946-; Giordani, Alessandro (Philosophische Analyse ;, 2018)
The series provides a forum for innovative, high-quality work in all fields of analytical philosophy. The volumes in this series are published in either English or German.